(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of research on the composition and bioecological characteristics of plant species in the flora of the Yozyovon State Nature Monument, with a focus on the bioecological properties of Populus pruinosa Schrenk, a species found in this flora.